Streamlining the Procurement Lifecycle: An Integrated Web-Based Platform for PPMP Consolidation and Document Tracking - Rommel S. Pabustan; Alaina Thea V. Concepcion (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
The research dealt with the impracticality of the manual administrative procedure, as they came up with a research titled; "Streamlining the Procurement Lifecycle: An Integrated Web-Based System to Consolid and Track Documents in PPMP." The study was aimed at the digitalization of the entire end-to-end procurement process, i.e. through automating the consolidation of multi-campus Project Procurement Management Plans (PPMPs) and real-time tracking of document status. To accomplish this, it has been developed using the Iterative and Incremental Development (IID) model that enabled progress through the constant improvement of requirement, design, implementation, and testing activities. Field experts and end-users tested the system with the help of a research instrument based on the ISO /IEC 25010:2023 product quality framework. The interpretation of the data involved the use of a five-point Likert scale, with the resultant Grand Mean of 4.25, according to which the answer is Strongly Agree. It means that the platform proves to be the most effective in all the dimensions considered with the Security scoring the best mean of 4.35. The findings substantiate the fact that the integrated platform manages to simplify the procurement lifecycle by increasing the data integrity and drop in the administrative lead times. The paper identifies this recommendation to use this web-based solution as an alternative to the old manual systems and proposes its future interconnection with larger financial management environments.